Risk Management Analysis with Enterprise Risk Management (ERM) at UMKM Maestro Gelato in Karawang Regency - Nur Agustin, Siska; Uus Mohammad Darul Fadli (Research in Management of Technology and Business, 2024)
This study aims to identify how implementing Risk Management can assist in managing and reducing potential operational risks. Risk management is used to analyze risks classified as low risk, medium risk, and high risk at UMKM Maestro Gelato. The Enterprise Risk Management (ERM) approach of the ISO 31000: 2009 guideline version is the research method used. This research also discusses the effect of Risk Management on predicting risks that can cause businesses to experience financial losses and other possible threats. This Enterprise Risk Management (ERM) approach uses 5 components of risk identification. The results of this study found 17 risks grouped into operational risk, financial risk, strategic risk, and hazard risk. With standardized Risk Management procedures and periodic evaluations, UMKM Maestro Gelato can avoid risks in running a business in the future.